Residential water consumption pattern and internal uses of water - Barreto, Douglas (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This article presents the results of a research study results ofon the residential water consumption pattern and its internal uses. The research investigation was carried out in a sample of residences households in the west zone of São Paulo city. A historical brief literature review on research was developed and as well the state of arts in technical papers that oriented the research, methodology and equipments utilized in order to obtain the residential household water consumption pattern and internal uses of water is presented. The results are showed in tables and graphics where can be identified the wWater profile and internal uses of sanitary appliances results pointing indicate that e the shower with accounts for 13,9.9% of total residential consumption, followed by the kitchen tap with 12,0.0%; normal clothes washing machine with 10,9.9%; clothes tanksmall washing machine 9,2.2%; tank laundry sink tap with connection with tap associated with clothes the washing machine 8,3.3%; wc pan with discharge tanktoilet cistern with 5,5.5%; tank laundry sink taptap 5,4.4%; e and lavatory tapbathroom sink tap with 4,2.2%. ; another uses with The remaining 30,6.6%. % corresponded to other uses. These results provide further knowledge onThe work done bring more knowledge about the theme considering the methodologies applied to find out the water consumptiomconsumption profile and residential water end uses. Also the results came out to engineering field news values about water consumptiom profile and residential water end uses.